Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.12997/jla.2020.9.2.243
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effects of O-GlcNAcylation in Vascular Smooth Muscle Cells on Diabetic Vasculopathy

Abstract: Vascular complications from uncontrolled hyperglycemia are the leading cause of death in patients with diabetes mellitus. Previous reports have shown a strong correlation between hyperglycemia and vascular calcification, which increases mortality and morbidity in individuals with diabetes. However, the precise underlying molecular mechanisms of hyperglycemia-induced vascular calcification remain largely unknown. Transdifferentiation of vascular smooth muscle cells (VSMC) into osteoblast-like cells is a known c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 82 publications
(94 reference statements)
0
15
0
Order By: Relevance
“…Previous studies showed VC is the main independent risk factor for morbidity and mortality of cardiovascular diseases with diabetes ( 29 , 30 ). Hyperglycemia and increased glycation end products, hyperinsulinemia, oxidative stress, lipid metabolism disturbance, inflammation, apoptosis and abnormal expression of bone regulatory protein are the main factors of vascular calcification in T2DM, which are closely related to the occurrence and development of vascular calcification ( 31 , 32 ). In a population-based multi-ethnic cohort ( 33 ), Katz et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed VC is the main independent risk factor for morbidity and mortality of cardiovascular diseases with diabetes ( 29 , 30 ). Hyperglycemia and increased glycation end products, hyperinsulinemia, oxidative stress, lipid metabolism disturbance, inflammation, apoptosis and abnormal expression of bone regulatory protein are the main factors of vascular calcification in T2DM, which are closely related to the occurrence and development of vascular calcification ( 31 , 32 ). In a population-based multi-ethnic cohort ( 33 ), Katz et al.…”
Section: Discussionmentioning
confidence: 99%
“…O-GlcNAcylation promotes osteoblastic differentiation with enhanced expression of bonerelated markers such as alkaline phosphatase, osteocalcin, and bone sialoprotein via transcriptional activation of runt-related transcription factor 2 (Runx2), an osteogenic transcription factor. O-GlcNAcylation of Runx2 stimulated mineralization of extracellular matrix [188]. Furthermore, increased O-GlcNAcylation levels reduce endothelium-dependent relaxation through the overproduction of ROS via activation of NADPH oxidase [189].…”
Section: O-glcnacylation and Vascular Remodelingmentioning
confidence: 99%
“…In this sense, there is direct evidence that elevated levels of protein O-GlcNAcylation in endothelial cells impairs endothelium-dependent relaxation ( 44 , 47 49 ), demonstrating that O-GlcNAcylation leads to endothelial dysfunction. Furthermore, O-GlcNAcylation of vascular smooth muscle cells augments vascular response to contractile agonists ( 50 , 51 ) and favors vascular calcification ( 52 54 ), resulting in high blood pressure ( 25 ).…”
Section: O-glcnacylation and Arterial Hypertensionmentioning
confidence: 99%